(Fe, Co)/N‐Doped Multi‐Walled Carbon Nanotubes as Efficient Bifunctional Electrocatalysts for Rechargeable Zinc‐Air Batteries. Issue 3 (18th December 2020) - Qi, Yugang; Yuan, Shan; Cui, Lili; Wang, Zizhun; He, Xingquan; Zhang, Wei; Asefa, Tewodros
Abstract: The design and fabrication of efficient, less costly, and stable bifunctional oxygen electrode electrocatalysts is crucial for large‐scale production of rechargeable zinc‐air batteries. Herein, electrocatalytically active, hybrid materials composed of Fe−Co alloy nanoparticles‐embedded N‐doped carbon nanotubes (CNTs) are synthesized from Fe/Co‐polyporphyrin‐CNTs via pyrolysis. The materials serve as highly effective bifunctional oxygen electrode catalysts for zinc‐air batteries. In particular, the one synthesized at 700 °C, named CNTs@(Fe, Co)PP‐700, shows a very good activity for both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in an alkaline solution. This material catalyzes ORR with a limiting current density of 5.11 mA cm −2 and a half‐wave potential of 0.86 V vs RHE. It also catalyzes OER with 10 mA cm −2 at a small overpotential of 360 mV. Besides, it operates well as an air cathode in a home‐made rechargeable zinc‐air battery, with a small voltage gap of 0.71 V at 2 mA cm −2, while remaining stable in hundreds of charge‐discharge cycles for >83 h. Its performance in a zinc‐air battery is better than that of a benchmark air‐electrode containing noble metals, Pt/C+RuO2 . Abstract : Peak Power ! Novel hybrid materials composed of N‐doped carbon nanotubes (CNTs) with several embedded Fe−Co alloy nanoparticles (CNTs@(Fe, Co)PP) that can serve as highly efficient bifunctional oxygen electrocatalysts are derived from bimetallic Fe/Co‐coordinated polyporphyrin‐CNTs self‐assemblies via pyrolysis. The optimal electrocatalyst is used at air electrode in zinc‐air battery (ZAB) delivering a higher peak power density and showing a better long‐term cycling stability than a ZAB containing the noble metal electrocatalysts Pt/C+RuO2 .